Highway engineering : planning, design, and operations - Findley, Daniel J. (Daniel Jonathan); Cunningham, Christopher M.; Brown, Thomas H., Jr. (Thomas Hunter), 1947-; Cahill, Lorraine M.; Yan, Guangchuan; Huntsinger, Leta F. (Butterworth-Heinemann, 2022)
Highway Engineering: Planning, Design, and Operations, Second Edition, presents a clear and rigorous exposition of highway engineering concepts, including project development and the relationship between planning, operations, safety and highway types. The book includes important topics such as corridor selection and traverses, horizontal and vertical alignment, design controls, basic roadway design, cross section elements, intersection and interchange design, and the integration of new vehicle technologies and trends. It also presents end of chapter exercises to further aid understanding and learning. This edition has been fully updated with the current design policies and reference manuals essential for highway, transportation, and civil engineers who are required to work to these standards.